Soil ingestion and lead concentration in wildlife species - Connor, Erin E. (Virginia Tech, 1993)
Problems related to estimating soil ingestion by wildlife species from analysis of feces were examined. Soil ingestion was investigated as a means by which wildlife may be exposed to environmental contaminants, particularly Pb. Titanium (Ti) and acid-insoluble residue (AIR) tracer methods for estimating soil ingestion were compared. The two methods were not significantly (P > 0.05) different when diet consisted of 10% (dry weight, d.w.) soil. When diet contained 5% soil, soil ingestion was more accurately estimated using the Ti method. Digestibility of soil can be ignored in the equation for quantifying soil ingestion from analysis of feces. Soil ingestion, as percentage dry matter intake (% DMI), by five wildlife species was estimated from analysis of feces or intestinal contents using the Ti tracer method. Soil ingestion by mourning doves (Zenaida macroura) was estimated using AIR analysis of crop contents. Mean ( S.E.) soil ingestion by Canada geese (Branta canadensis) and mallards (Anas platyrhynchos) were 4.92 ( 0.60) and 11.73 ( 1.54), respectively. Diets of short-tailed shrews (Blarina brevicauda) consisted of 5.20 ( 1.87)% soil, white-footed mice (Peromyscus leucopus) 16.21 ( 4.85)%, meadow voles (Microtus pennsylvanicus) 2.01 ( 0.34)%, and mourning doves 0.83 ( 0.41)% soil. Mallards collected from Killarney Lake, northern Idaho were analyzed for free erythrocyte protoporphyrin, fecal, liver, and kidney Pb concentrations, and soil/sediment ingestion. Sediment from the area contained 4485 ppm Pb (d.w.). Protoporphyrin was a poor indicator of Pb contamination at this level of exposure and/or under these conditions. Soil/sediment ingestion by mallards averaged 7.5% DMI. Tissue Pb concentrations indicated mallards were suffering from chronic exposure to low concentrations of Pb. Sediment collected from Killarney Lake (4485 ppm Pb) was fed to northern bobwhites (Colinus virginianus) at 8% DMI for 21 dad. Lead concentrations in blood, liver, and kidneys were determined and compared to control values. ...